Bioavailability of plant pigment phytochemicals in Angelica keiskei in older adults: A pilot absorption kinetic study - Corrêa, Camila Renata [UNESP]; Chen, C-Y. Oliver; Aldini, Giancarlo; Rasmussen, Helen; Ronchi, Carlos F. [UNESP]; Berchieri-Ronchi, Carolina [UNESP]; Cho, Soo-Muk; Blumberg, Jeffrey B.; Yeum, Kyung-Jin (Korean Nutrition Soc, 2014)
BACKGROUND/OBJECTIVES: Angelica keiskei is a green leafy vegetable rich in plant pigment phytochemicals such as flavonoids and carotenoids. This study examined bioavailability of flavonoids and carotenoids in Angelica keiskei and the alteration of the antioxidant performance in vivo.SUBJECTS AND MATERIALS: Absorption kinetics of phytochemicals in Angelica keiskei were determined in healthy older adults (>60 y, n = 5) and subjects with metabolic syndrome (n = 5). Subjects consumed 5 g dry Angelica keiskei powder encapsulated in gelatin capsules with a low flavonoid and carotenoid liquid meal. Plasma samples were collected at baseline, 0.5, 1, 2, 3, 4, 5, 6, 7, and 8 h. Samples were analyzed for flavonoids and carotenoids using HPLC systems with electrochemical and UV detection, respectively, and for total antioxidant performance by fluorometry.RESULTS: After ingestion of Angelica keiskei increases in plasma quercetin concentrations were observed at 1-3 and 6-8 hr in the healthy group and at all time points in the metabolic syndrome group compared to baseline (P < 0.05). Plasma lutein concentrations were significantly elevated in both the healthy and metabolic syndrome groups at 8 hr (P < 0.05). Significant increases in total antioxidant performance were also observed in both the healthy and the metabolic syndrome groups compared to baseline (P < 0.05).CONCLUSIONS: Findings of this study clearly demonstrate the bioavailability of phytonutrients of Angelica keiskei and their ability to increase antioxidant status in humans.
Keywords: Angelica keiskei; quercetin; lutein; absorption kinetic; total antioxidant performance